UiO-66-based Photocatalysts for CO2 to Methanol Conversion Potential: Mechanisms and Performance Benchmarks - Septian Wahyu Setiawan; Ummi Aminatus Sa'diyah; Silvana Dwi Nurherdiana; Novia Amalia Sholeha; Hamzah Fansuri; Djoko Hartanto (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
The increasing concentration of carbon dioxide (CO2) emissions has driven the development of technologies for converting CO2 into environmentally friendly fuels through photocatalytic reduction. One of the widely studied materials is UiO-66, a metal–organic framework (MOF)-based photocatalyst. This article presents a literature review aimed at analyzing recent research developments on the application of UiO-66 for CO2 reduction. Relevant studies were systematically collected from Scopus, ScienceDirect, and Google Scholar databases within the 2015–2025 period, focusing on experimental investigations and material modifications. The synthesis of the reviewed studies indicates that the photocatalytic performance of UiO-66 is influenced by metal modification, functional group incorporation, band gap engineering, and the use of co-catalysts. These strategies enhance visible light absorption and improve the effectiveness of light energy utilization, thereby promoting CO2 reduction activity. Although UiO-66 demonstrates promising potential, improvements in material stability and reaction performance consistency remain necessary for large-scale industrial applications. Contribution to Sustainable Development Goals (SDGs):SSDG 7: Affordable and Clean EnergySDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 13: Climate Action